The rheological and mechanical properties of 3D-printed geopolymers: A review - Tanyildizi, Harun; Seloglu, Maksut; Abdullah, Mohd Mustafa Al Bakri; Razak, Rafiza Abdul; Mydin, Md Azree Othuman (Elsevier, 2025)
Geopolymer has become an alternative binder to cement in recent years. While producing cement, approximately 0.8 tons of CO2 is released to produce one ton of clinker. The cement industry causes about 5-8 % of the world's greenhouse gases to be released. Therefore, it is necessary to reduce the carbon footprint of the cement industry. Geopolymers are defined as ecofriendly since they have approximately 80 % lower CO2 emissions than cement. In addition, studies have been carried out by many researchers in recent years since geopolymers have high strength and durability properties. In the last ten years, three-dimensional (3D) printers, which are a new technology, have been included in the construction sector. 3D printers are preferred because of their lower material consumption, less waste, no need for molds, faster construction, and reducing occupational accidents. Due to these advantages, the rheological and mechanical properties of 3D-printed geopolymer concrete and geopolymer mortar were briefly discussed in this review. This article summarizes the challenges and practical limitations of 3D printed geopolymers and summarizes the innovations to date to provide a theoretical basis for the development of 3D printed geopolymers.
Keywords: 3D-printed geopolymers; Rheology; Mechanical properties